Eksistensi Nilai-Nilai Pendidikan Karakter Siswa Sekolah Dasar - Ari Susandi; Siti Mas'ula; Budi Setiawan; Aries Dirgayunita; Yulina Fadilah (Universitas Negeri Malang, 2022)
This study aims to explore the existence of character education values for elementary school students with online learning and door to door learning system, by choosing descriptive qualitative as its implementation. The research location was MI Muhammadiyah 1 Probolinggo City. The informants in this study were teachers from grade 1 to grade 3, totaling six people. This study used a phenomenological type of research. Data obtained by direct observation, interviews and documentation. Data analysis was carried out through data reduction, data display, and verification. The results of this study are (1) teachers must be able to provide an online learning system to support the existence of character education values for elementary school students during online learning; (2) collaboration of online learning with door to door provides enormous benefits in the development of the character values; (3) the role of teachers in learning innovation and collaboration with parents can help optimizing the development and habituation of the character values in students. Penelitian ini bertujuan untuk mengeksplorasi eksistensi nilai-nilai pendidikan karakter siswa sekolah dasar dengan sistem pembelajaran online dan door to door, dengan memilih deskriptif kualitatif sebagai implementasinya. Tempat penelitian adalah MI Muhammadiyah 1 Kota Probolinggo. Informan dalam penelitian ini adalah guru kelas 1 hingga kelas 3 yang berjumlah enam orang. Penelitian ini menggunakan jenis penelitian fenomenologi. Data didapatkan dengan observasi langsung, wawancara serta dokumentasi. Analisis data dilakukan melalui reduksi data, display data, juga verifikasi. Hasil dari penelitian ini meliputi, (1) guru harus mampu mengembangkan sistem pembelajaran online untuk mendukung eksistensi nilai-nilai pendidikan karakter siswa sekolah dasar selama pembelajaran online; (2) kolaborasi pembelajaran secara daring atau online dengan door to door ini memberikan manfaat yang sangat besar dalam pengembangan nilai karakter; (3) peran guru dalam inovasi pembelajaran dan kerja sama dengan orang tua dapat membantu mengoptimalkan perkembangan dan pembiasaan nilai karakter dalam diri siswa.